Thomas the Twin: Constructing an Apostolic Personality - Cooper, Adam (New blackfriars, 2025)
In the Synoptic Gospels and Acts, Thomas is mentioned only in the four lists of the Apostles (Mk 3:18; Mt 10:3; Lk 6:15; Ac 1:13). Appearing about midway through these lists, he seems to have been regarded as relatively unimportant among the Twelve. By contrast, in John’s Gospel, Thomas is presented as a central character, featuring prominently in four major scenes. In three of those scenes Thomas is given the additional name Didymus (Twin), a name exclusive to him in John’s Gospel and later tradition, especially in connection with Syrian Edessa. By the 4th century, Edessa had become famous for its special veneration of the Apostle Thomas, with sources featuring Thomas as the missionary link between Jesus and the early Christianisation of lands from Syria to India. The Edessan School of Thomas developed an encratic school of devotion to Thomas as the mystical twin of Jesus and prototypical Christian healer, and the Syrian city housed an established shrine for his remains. Scholars rightly contest the historical value of these sources, but analysis of their provenance, content and reception allows us to outline a picture whose lines converge in a coherent and plausible tradition of devotion that, in just a few centuries, reached as far east as India and as far west as Spain, Gaul, and Britain.